Reference Ranges for Ultrasonographic Measurements of the Uterine Cervix in Low-Risk Pregnant Women - Andrade, Kleber Cursino; Bortoletto, Thaísa Guedes; Almeida, Cristiane Martins; Daniel, Renan Antonio; Avo, Heloísa; Pacagnella, Rodolfo Carvalho; Cecatti, José Guilherme (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective To define transvaginal ultrasound reference ranges for uterine cervix measurements according to gestational age (GA) in low-risk pregnancies.Methods Cohort of low-risk pregnant women undergoing transvaginal ultrasound exams every 4 weeks, comprising measurements of the cervical length and volume, the transverse and anteroposterior diameters of the cervix, and distance from the entrance of the uterine artery into the cervix until the internal os. The inter- and intraobserver variabilities were assessed with the linear correlation coefficient and the Student t-test. Within each period of GA, 2.5, 10, 50, 90 and 97.5 percentiles were estimated, and the variation by GA was assessed with analysis of variance for dependent samples. Mean values and Student t-test were used to compare the values stratified by control variables.Results After confirming the high reproducibility of the method, 172 women followed in this cohort presented a reduction in cervical length, with an increase in volume and in the anteroposterior and transverse diameters during pregnancy. Smaller cervical lengths were associated with younger age, lower parity, and absence of previous cesarean section (C-section).Conclusion In the studied population, we observed cervical length shortening throughout pregnancy, suggesting a physiological reduction mainly in the vaginal portion of the cervix. In order to better predict preterm birth, cervical insufficiency and premature rupture of membranes, reference curves and specific cut-off values need to be validated.
Keywords: ultrasound; uterine cervix; cervical length; reference ranges; low-risk pregnancy